The level of employment of female leaders for (IT) services, and the challenges they face from their point of view - Al-Zahrani, Huda Abdullah; Alabbasi, Dalal Omar (Journal of Educational and Psychological Sciences, 2022)
The aim of this descriptive study is to find out the level of employment of female leaders for (IT) services in Jeddah governorate, and to reveal the challenges they face from their point of view through these variables (academic qualification, years of experience of the female leader in school administrating, training courses in (IT). To achieve that, the researcher designed a questionnaire of (39) elements, distributed to the sample of the study, which consisted of (235) female leaders. The study showed that the level of employment of female leaders for information technology services was (high) with an average of (4.13). At the level of sub- fields; Where it was found that the field of employing technology in the administrative process was (very high), and that the field of employing technology in the educational process was (high), and that the challenges faced by the female leaders in employing information technology were (medium) in general, with an average of (3.19) at the level of the two sub- fields (the administrative process, and educational process). There are statistically significant differences at the level of (α ≤ 0.05) due to the variables obtaining training courses, in favor of those who got training courses (more than 10), and there are statistically significant differences due to the variable of experience in school administration in favor of those with experience (more than from 12 years), while there were no statistically significant differences due to the variable of the educational qualification. The researcher recommended holding more training courses in the field of technology and using advanced technical means to connect to the Internet via satellite, to solve the problems facing schools and to do more studies to find out the level of employment of technology in public schools in different regions and governorates, and studies that reveal the challenges of employing technology in the educational process in Jeddah in particular and the kingdom of Saudi Arabia in general.
Keywords: Information Technology; Technology; Internet; Challenges; Kingdom of Saudi Arabia; Education